Drexel dragonThe Math ForumDonate to the Math Forum

Ask Dr. Math - Questions and Answers from our Archives
_____________________________________________
Associated Topics || Dr. Math Home || Search Dr. Math
_____________________________________________

Completing the Square: How Does it Work?


Date: 01/20/99 at 16:36:14
From: Dena
Subject: Completing the Square

I don't understand how to complete the square. Am I right that you are 
supposed to divide the second term by two and then square it? I always 
get messed up when there are fractions. Please help!


Date: 01/23/99 at 20:04:23
From: Doctor Jeremiah
Subject: Re: Completing the Square

Hi Dena:

Yes, you are right about the procedure. Let me try to show you why:

When we complete the square the whole goal is to get the equation into 
a form so that it can be simplified into a square. Say we start with 
ax^2 + bx + c = 0. The idea is to translate that into (x + d)^2 = e.
But (x + d)^2 = e when expanded is x^2 + 2dx + d^2 = e:

   ax^2 + bx + c = 0 ==> (x + d)^2 = e ==> x^2 + 2dx + d^2 = e

The first step in this is to get rid of the factor on the x^2 term:

         ax^2 + bx + c = 0
   ax^2/a + bx/a + c/a = 0/a
      x^2 + bx/a + c/a = 0

Now we substitute 2d for b/a because when we complete the square these 
terms must be equal:

   2d = b/a
    d = b/(2a)
  d^2 = (b/(2a))^2

And if you look at the numeric term carefully, the c changes to d^2-e:

   c/a = d^2 - e
     e = d^2 - (c/a) <== d^2 = (b/(2a))^2
     e = (b/(2a))^2 - (c/a)

Now if we put it all together:

   ax^2 + bx + c = 0 ==> x^2 + bx/a + (b/(2a))^2 = (b/(2a))^2 - (c/a)

And if you look at this you'll see that you were exactly right in 
saying that the third term is the second term divided by two and then 
squared. The important thing to notice is that the value on the right 
of the equals sign changes.

For example, say the equation we have is:

   x^2 + 6x - 16 = 0

Then if we move the 16 to the right side:

        x^2 + 6x = 16

Now to find the real third term. (6/2)^2 = 9. But remember you need to 
add it to both sides:

    x^2 + 6x + 9 = 16 + 9
    x^2 + 6x + 9 = 25
         (x+3)^2 = 25

If you need me to explain better why it works, just write back.

- Doctor Jeremiah, The Math Forum
  http://mathforum.org/dr.math/   
    
Associated Topics:
High School Basic Algebra
High School Polynomials
Middle School Algebra
Middle School Factoring Expressions

Search the Dr. Math Library:


Find items containing (put spaces between keywords):
 
Click only once for faster results:

[ Choose "whole words" when searching for a word like age.]

all keywords, in any order at least one, that exact phrase
parts of words whole words

Submit your own question to Dr. Math

[Privacy Policy] [Terms of Use]

_____________________________________
Math Forum Home || Math Library || Quick Reference || Math Forum Search
_____________________________________

Ask Dr. MathTM
© 1994-2013 The Math Forum
http://mathforum.org/dr.math/